PERCENTAGE OF BONELESS MEAT OF JAWA SUPER NATIVE CHICKEN WERE GIVEN CITRONELLA MEAL (Cymbopogon nardus) IN THE RATION: PERSENTASE DAGING NIRTULANG AYAM KAMPUNG JAWA SUPER YANG DIBERI TEPUNG SERAI WANGI (CYMBOPOGON NARDUS) DALAM RANSUM - Diwangkara, Catra; Ristika Handarini; Mohammad Winugroho (Jurnal Peternakan Nusantara, 2024)
Jawa super native chickens are the result of a cross between native chickens and laying hens. Super native chickens have the advantage of greater body weight and faster growth. Citronella is one of the grass plants that contains saponins, flavonoids, and polyphenols that have antiseptic properties for the digestive tract of chickens and increase feed palatability. This study aims to provide information to the public to assess the effect of using citronella flour on the growth of commercial weight of super native chickens. This research was conducted on July 26 - September 26, 2023, at Padasuka Village, Ciomas, Bogor. This study used a completely randomized design (CRD) with 5 treatments and 4 replicates with a total of 100 DOC. Data were analyzed using analysis of variance (ANOVA) and Duncan’s further test. R0 = Control ration, R1 = addition of 2% citronella meal in ration, R2 = addition of 4% citronella meal in ration, R3 = addition of 6% citronella meal in ration, R4 = addition of 8% citronella meal in ration. The variables observed in this study were the percentage of breast and thigh, the percentage boneless of breast and thigh, the percentage bone of breast and thigh, the percentage skin of breast and thigh, and the ratio of bone and meat breast and thigh. The result of this research is that the provision of citronella flour at a concentration level between 2 to 8% has not shown a significant effect on the percentage of meat and bone on the breast and thigh, the percentage of bone on the breast and thigh, the percentage of skin on the breast and thigh, and the ratio of meat and bone on the breast and thigh in joper native chickens. However, citronella meal had a tendency to increase the boneless percentage in free-range chickens with a concentration of 6%.